Preparation method and application of ion skeleton with selective adsorption

By using the ionic framework constructed by Na+ and Anderson type polymetal oxygen clusters, the problem of inefficiency in traditional adsorption methods when dealing with acidic and alkaline gases is solved, and efficient selective adsorption of SO2 and NH3 is achieved, which significantly broadens the polymetal oxygen Clusters are used in the field of gas adsorption.

CN119390994APending Publication Date: 2025-02-07JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411497864.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When traditional adsorption methods treat acidic and alkaline gases simultaneously, it may be difficult to achieve efficient purification.

Method used

An ionic framework with a microporous structure composed of Na+ and Anderson type polymetal oxygen clusters was prepared by modification of triol ligands.

Benefits of technology

These ionic frameworks exhibit excellent heat, humidity and organic solvent stability, have strong adsorption capacity for polar bond gases such as SO2 and NH3, and have almost no adsorption to non-polar or weak polar gases, showing high selection sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390994A_ABST
    Figure CN119390994A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of adsorption materials, and provides a preparation method and application of an ion skeleton with selective adsorption. According to the invention, a series of ion skeletons with microporous structures are constructed by using the Anderson type polyoxometalate modified by the triol ligand and Na < + >, and the skeletons show excellent heat, humidity and organic solvent stability and are very suitable for being used as gas adsorbents. Especially, the composite material shows very strong adsorption capacity on SO2, NH3 and other polar bond gases, almost has no adsorption on non-polar or weak-polar gases, and shows high selectivity. The invention not only provides a new material and thought for selective adsorption of gases with polar bonds, is expected to be further expanded to adsorption treatment of more toxic gases, but also remarkably widens the application range of the polyoxometalate in the field of gas adsorption, and points out a new direction for development of innovative gas adsorbents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a preparation method and application of an ionic skeleton with selective adsorption. Background Art

[0002] In the process of modern industrialization and urbanization, the problem of toxic gas emissions is becoming increasingly serious, seriously affecting environmental quality and human health, so it is particularly important to effectively manage toxic gases. By adopting reasonable technical means to remove toxic substances from the air, it is not only possible to improve environmental quality, but also to protect ecological balance and human health. There are many methods for treating toxic gases, including physical, chemical and biological methods. Among these methods, adsorption has attracted much attention because of its simplicity and cost-effectiveness. The adsorption method uses active sites on the surface and inside of solid materials to adsorb gas molecules, thereby achieving the purpose of removal. This method shows good treatment effects in practical applications and has become an important means of managing toxic gases. The advantage of using adsorption to treat toxic gases is its flexibility and adaptability, and different adsorbent materials can be selected according to the characteristics of different gases. In addition, the adsorption method is usually simple to operate, low cost, and can efficiently remove various gases. However, traditional adsorption methods also have obvious limitations, especially when treating acidic and alkaline gases at the same time, it may be difficult to achieve efficient purification. To this end, the present invention proposes a preparation method and application of a class of ionic skeletons with selective adsorption. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing an ionic skeleton with selective adsorption and its application, aiming to solve the problems raised in the above background technology.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A method for preparing an ionic framework with selective adsorption, wherein the ionic framework is composed of Na + and Anderson type polymetallic oxygen clusters, the ionic framework comprising:

[0006] Fe-Et, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [FeMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O;

[0007] Co-Et, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [CoMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O;

[0008] Ni-Et, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [NiMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O;

[0009] Cu-Et, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [CuMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O;

[0010] Fe-OH, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [FeMo6O 18 [HOCH2C(CH2O)3]2];

[0011] Co-OH, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [CoMo6O 18 [HOCH2C(CH2O)3]2];

[0012] Ni-OH, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [NiMo6O 18 [HOCH2C(CH2O)3]2];

[0013] Cu-OH, whose molecular formula is Na 2 / 3 (NH4) 10 / 3 [CuMo6O 18 [HOCH2C(CH2O)3]2];

[0014] The preparation steps of Fe-Et are as follows: 2mmol FeSO4·7H2O, 2mmol (NH4)6Mo7O 24 4H2O and 4mmol 1,1,1-trimethylolpropane were dissolved in 23mL buffer solution of CH3COONa / CH3COOH, and the mixture was heated to 80°C for 2h under continuous stirring; then, it was filtered in a hot state to obtain a filtrate; the filtrate was evaporated by leaving it open at room temperature for 2 days to obtain crystals;

[0015] The preparation step of Co-Et is as follows: replacing FeSO4·7H2O in the preparation step of Fe-Et with CoSO4·7H2O;

[0016] The preparation steps of Ni-Et are as follows: replacing FeSO4·7H2O in the preparation step of Fe-Et with NiSO4·6H2O;

[0017] The preparation step of Cu-Et is as follows: replacing FeSO4·7H2O in the preparation step of Fe-Et with CuSO4·5H2O;

[0018] The preparation step of the Fe-OH is as follows: replacing 1,1,1-trimethylolpropane in the preparation step of Fe-Et with pentaerythritol;

[0019] The preparation step of Co-OH is as follows: replacing 1,1,1-trimethylolpropane in the preparation step of Co-Et with pentaerythritol;

[0020] The preparation step of Ni-OH is as follows: replacing 1,1,1-trimethylolpropane in the preparation step of Ni-Et with pentaerythritol;

[0021] The preparation step of Cu-OH is as follows: 1,1,1-trimethylolpropane in the preparation step of Cu-Et is replaced by pentaerythritol.

[0022] A type of ionic framework with selective adsorption prepared according to the preparation method described above is used as a gas adsorbent in the adsorption of gases with polar bonds, and the gases with polar bonds include SO2 and NH3.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention utilizes triol ligand-modified Anderson-type polyoxometalates and Na + A series of ionic skeletons with microporous structures have been constructed. These skeletons show excellent thermal, humidity and organic solvent stability, and are very suitable for use as gas adsorbents. In particular, they show strong adsorption capacity for polar bond gases such as SO2 and NH3, and almost no adsorption for non-polar or weakly polar gases, showing high selectivity. The present invention not only provides new materials and ideas for the selective adsorption of gases with polar bonds, which is expected to be further expanded to the adsorption treatment of more toxic gases, but also significantly broadens the application scope of polymetallic oxygen clusters in the field of gas adsorption, and points out a new direction for the development of innovative gas adsorbents. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the structure of Cu-Et and Cu-OH; (a) anion {CuMo6O 18 [CH3CH2C(CH2O)3]2} 4- Around Na + The distribution of (b) Na +Distribution of surrounding anions; (c) Repeating unit of Cu-Et; (d) Schematic diagram of the structure of the repeating unit; (e) Three-dimensional stacking structure of Cu-Et; (f) Anion {CuMo6O 18 [HOCH2C(CH2O)3]2} 4- Around Na + Distribution; (g) dodecaned anion structure in Cu-OH; (h) three-dimensional stacking structure of Cu-OH.

[0026] Figure 2 Fourier transform infrared spectra of M-Et and M-OH (M=Fe, Co, Ni, Cu).

[0027] Figure 3 Thermal gravimetric curves of M-Et and M-OH (M=Fe, Co, Ni, Cu).

[0028] Figure 4 Powder diffraction patterns of M-Et and M-OH (M=Fe, Co, Ni, Cu) before and after heating.

[0029] Figure 5 Powder diffraction patterns of M-Et and M-OH (M=Fe, Co, Ni, Cu) at different humidity.

[0030] Figure 6 Powder diffraction patterns of M-Et and M-OH (M=Fe, Co, Ni, Cu) after immersion in different solvents.

[0031] Figure 7 Nitrogen adsorption-desorption curves and pore size distribution of Cu-Et and Cu-OH; (a) Nitrogen adsorption-desorption curve of Cu-Et; (b) Pore size distribution of Cu-Et; (c) Nitrogen adsorption-desorption curve of Cu-OH; (d) Pore size distribution of Cu-OH.

[0032] Figure 8 Isothermal adsorption curves of SO2 and NH3 of M-Et and M-OH (M=Fe, Co, Ni, Cu) at 273K and the adsorption amount at 1bar; (a) isothermal adsorption curve of SO2; (b) adsorption amount of SO2 at 1bar; (c) isothermal adsorption curve of NH3; (d) adsorption amount of NH3 at 1bar.

[0033] Fig. 9 These are the SO2 adsorption-desorption curves of M-Et and M-OH (M=Fe, Co, Ni, Cu).

[0034] Fig.10 These are the NH3 adsorption-desorption curves of M-Et and M-OH (M=Fe, Co, Ni, Cu).

[0035] Fig.11 These are the adsorption curves of Cu-OH for SO2, CO, O2, CH4 and NH3, N2, H2; (a) SO2, CO, O2, CH4 adsorption curve; (b) NH3, N2, H2 adsorption curve.

[0036] Fig.12 The adsorption curves of Fe-OH, Co-OH, Ni-OH and Cu-Et for SO2, CO, O2 and CH4; (a) The adsorption curve of Fe-OH for SO2, CO, O2 and CH4; (b) The adsorption curve of Co-OH for SO2, CO, O2 and CH4; (c) The adsorption curve of Ni-OH for SO2, CO, O2 and CH4; (d) The adsorption curve of Cu-Et for SO2, CO, O2 and CH4.

[0037] Fig.13 The adsorption curves of Fe-OH, Co-OH, Ni-OH and Cu-Et for NH3, N2, and H2; (a) The adsorption curve of Fe-OH for NH3, N2, and H2; (b) The adsorption curve of Co-OH for NH3, N2, and H2; (c) The adsorption curve of Ni-OH for NH3, N2, and H2; (d) The adsorption curve of Cu-Et for NH3, N2, and H2.

[0038] Fig.14 Gas penetration curves of Cu-OH for mixed gases SO2 / CO, SO2 / O2, SO2 / CH4, NH3 / N2, and NH3 / H2 (volume ratio of 3:97) and the corresponding breakthrough points of the mixed gases; (a) gas penetration curve of SO2 / CO; (b) gas penetration curve of SO2 / O2; (c) gas penetration curve of SO2 / CH4; (d) gas penetration curve of NH3 / N2; (e) gas penetration curve of NH3 / H2; (f) corresponding breakthrough points of the mixed gases.

[0039] Fig.15 Gas penetration curves of Cu-OH for mixed gases SO2 / CO, SO2 / O2, SO2 / CH4, NH3 / N2, and NH3 / H2 (volume ratio of 50:50); (a) gas penetration curve of SO2 / CO; (b) gas penetration curve of SO2 / O2; (c) gas penetration curve of SO2 / CH4; (d) gas penetration curve of NH3 / N2; (e) gas penetration curve of NH3 / H2.

[0040] Fig.16 These are the diffraction spectra of M-Et and M-OH (M=Fe, Co, Ni, Cu) powders before and after adsorption of SO2.

[0041] Fig.17These are the diffraction spectra of M-Et and M-OH (M=Fe, Co, Ni, Cu) powders before and after adsorption of NH3.

[0042] Fig.18 The adsorption-desorption curves of SO2 and NH3 after 5 cycles of Cu-OH and the powder diffraction spectra before and after the adsorption and desorption of SO2 and NH3; (a) the adsorption-desorption curve of SO2 after 5 cycles of Cu-OH; (b) the powder diffraction spectrum before and after the adsorption and desorption of SO2 by Cu-OH; (c) the adsorption-desorption curve of NH3 after 5 cycles of Cu-OH; (d) the powder diffraction spectrum before and after the adsorption and desorption of NH3 by Cu-OH.

[0043] Fig.19 These are the SO2 and NH3 adsorption-desorption curves of M-Me (M=Fe, Co, Ni, Cu).

[0044] Fig. 20 It is the adsorption amount of NH3 and SO2 of M-Me, M-Et and M-OH (M=Fe, Co, Ni, Cu) at 273K and 1bar.

[0045] Fig.21 The adsorption curves of SO2 and NH3 on Cu-OH at 273K and 298K; (a) The adsorption curve of SO2 on Cu-OH at 273K and 298K; (b) The adsorption curve of NH3 on Cu-OH at 273K and 298K.

[0046] Fig. 22 The adsorption energies of SO2 and NH3 on M-OH (M=Fe, Co, Ni, Cu) and the corresponding bar graphs; (a) The adsorption energies of SO2 and NH3 on M-OH; (b) The corresponding bar graph of part (a).

[0047] Fig.23 The adsorption energy of Cu-OH for CO, O2, CH4, N2, and H2 and the corresponding bar graphs; (a) The adsorption energy of Cu-OH for CO, O2, CH4, N2, and H2; (b) is the corresponding bar graph of part (a).

[0048] Fig.24 Isotherm adsorption curves of Cu-OH for H2S and C2H2. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0050] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0051] All of the following chemicals, including FeSO4·7H2O, CoSO4·7H2O, NiSO4·6H2O, CuSO4·5H2O, CH3COONa, CH3COOH, (NH4)6Mo7O 24 ·4H2O, 1,1,1-trimethylolpropane, and pentaerythritol were all obtained from Aladdin Biochemicals (Shanghai, China) and used as received.

[0052] Fourier transform infrared (FT-IR) spectra were obtained on a Bruker Vertex 80v spectrometer. Experiments were performed using a Bruker press with a resolution of 4 cm -1 , the wave number range is 400~4000cm -1 . The entire spectral scanning process was repeated 32 times. Elemental C, H, and N data were measured on an Elementar vario MICRO cube instrument. PLASMA-SPEC(I) (ElementalAnalysis Inc., Lexington, KY) inductively coupled plasma optical emission spectrometry was performed for Fe, Co, Ni, Cu, Na, and Mo. Thermogravimetric (TG) data were measured on a TA TGA550 with a temperature ramp rate of 10°C / min. Single crystal X-ray diffraction data were collected on a Bruker D8 Venture single crystal X-ray diffractometer equipped with a Mo-Cu dual target, with a test temperature of 298K. Powder X-ray diffraction (PXRD) data were measured on a Rigaku SmartLab3 powder X-ray instrument.

[0053] Example 1, Synthesis of ionic skeleton;

[0054] 1) Synthesize Na 4 / 3 (NH4) 8 / 3 [FeMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O(Fe-Et);

[0055] FeSO4·7H2O (0.56g, 2mmol), (NH4)6Mo7O 244H2O (2.47 g, 2 mmol) and 1,1,1-trimethylolpropane (0.54 g, 4 mmol) were dissolved in 23 mL of a buffer solution of CH3COONa / CH3COOH (pH = 4.8), and the mixture was heated to 80°C for 2 h with continuous stirring. Subsequently, filtration was performed in a hot state to obtain a light green filtrate. The filtrate was left at room temperature and slowly evaporated by leaving it open for about 2 days, gradually obtaining light green crystals with a yield of 60.1% calculated based on Mo. Elemental analysis of Fe-Et, calculated: C 11.23%, H 2.77%, N 2.91%, Na 2.38%, Fe 4.35 and Mo 44.83%. Found: C 11.37%, H 2.84%, N 2.98%, Na2.31%, Fe 4.32% and Mo 44.51%.

[0056] 2) Synthesize Na 4 / 3 (NH4) 8 / 3 [CoMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O(Co-Et);

[0057] The synthetic route was similar to that of Fe-Et except that CoSO4·7H2O was used instead of FeSO4·7H2O, producing orange-yellow crystals with a yield of 62.2% calculated based on Mo. Elemental analysis of Co-Et, calculated: C 11.20%, H 2.76%, N 2.91%, Na2.37%, Co 4.58%, and Mo 44.73%. Found: C 11.47%, H 2.99%, N 2.95%, Na2.29%, Co4.51%, and Mo 44.03%.

[0058] 3) Synthesize Na 4 / 3 (NH4) 8 / 3 [NiMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O(Ni-Et);

[0059] The synthetic route was similar to that of Fe-Et except that NiSO4·6H2O was used instead of FeSO4·7H2O, yielding green crystals with a yield of 62.1% calculated based on Mo. Elemental analysis of Ni-Et, calculated: C 11.20%, H 2.76%, N 2.91%, Na2.38%, Ni 4.56%, and Mo 44.73%. Found: C 11.57%, H 2.98%, N 2.93%, Na 2.33%, Ni4.48%, and Mo 44.21%.

[0060] 4) Synthesize Na 4 / 3 (NH4)8 / 3 [CuMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O(Cu-Et);

[0061] The synthetic route was similar to Fe-Et except that CuSO4·5H2O was used instead of FeSO4·7H2O, producing blue crystals with a yield of 65.2% calculated based on Mo. Elemental analysis of Cu-Et, calculated: C 11.16%, H 2.75%, N 2.90%, Na2.37%, Cu 4.92%, and Mo 44.57%. Found: C 11.49%, H 2.97%, N 3.01%, Na2.33%, Cu4.85%, and Mo 44.12%.

[0062] 5) Synthesize Na 4 / 3 (NH4) 8 / 3 [FeMo6O 18 [HOCH2C(CH2O)3]2](Fe-OH);

[0063] The synthetic route was similar to that of Fe-Et except that 4 mmol of pentaerythritol was used instead of 1,1,1-trimethylolpropane, yielding light green crystals in 57.2% yield calculated based on Mo. Elemental analysis of Fe-OH, calculated: C 9.50%, H 2.29%, N 2.96%, Na 2.42%, Fe 4.42%, and Mo 45.52%. Found: C 9.54%, H 2.61%, N 3.04%, Na 2.32%, Fe 4.22%, and Mo 45.23%.

[0064] 6) Synthesize Na 4 / 3 (NH4) 8 / 3 [CoMo6O 18 [HOCH2C(CH2O)3]2](Co-OH);

[0065] The synthetic route was similar to Co-Et except that 4 mmol pentaerythritol was used instead of 1,1,1-trimethylolpropane, yielding orange-yellow crystals with a yield of 58.5% calculated based on Mo. Elemental analysis of Co-OH, calculated: C 9.48%, H 2.28%, N 2.95%, Na 2.41%, Co 4.65%, and Mo 45.41%. Found: C 9.71%, H 2.48%, N 3.02%, Na 2.23%, Co 4.41%, and Mo 45.01%.

[0066] 7) Synthesize Na 4 / 3 (NH4) 8 / 3 [NiMo6O 18[HOCH2C(CH2O)3]2](Ni-OH);

[0067] The synthetic route was similar to that of Ni-Et except that 4 mmol of pentaerythritol was used instead of 1,1,1-trimethylolpropane, yielding green crystals in 58.0% yield calculated based on Mo. Elemental analysis of Ni-OH, calculated: C 9.48%, H 2.28%, N 2.95%, Na 2.41%, Ni 4.63%, and Mo 45.42%. Found: C 9.53%, H 2.41%, N 2.99%, Na 2.21%, Ni 4.40%, and Mo 45.21%.

[0068] 8) Synthesize Na 2 / 3 (NH4) 10 / 3 [CuMo6O 18 [HOCH2C(CH2O)3]2](Cu-OH);

[0069] The synthetic route was similar to that of Cu-Et except that pentaerythritol was used instead of 1,1,1-trimethylolpropane, yielding blue crystals in 63.6% yield calculated based on Mo. Elemental analysis of Cu-OH, calculated: C 9.44%, H 2.27%, N 2.94%, Na 2.40%, Cu 5.00%, and Mo 45.25%. Found: C 9.71%, H 2.50%, N 2.95%, Na 2.09%, Cu 4.82%, and Mo 44.97%.

[0070] Results: The crystal structures of the above eight compounds were determined by single crystal X-ray diffraction, and their crystal parameters and refinement details are given in Tables 1 and 2.

[0071] Table 1. Crystallographic parameters and refinement results of compounds M-Et (M = Fe, Co, Ni, Cu)

[0072]

[0073]

[0074] Table 2. Crystallographic parameters and refinement results of compounds M-OH (M = Fe, Co, Ni, Cu)

[0075]

[0076]

[0077] In Table 1 and Table 2, a R1=Σ||F o |-|F c || / Σ|F o|; b wR2=Σ[w(F o 2 -F c 2 ) 2 ] / Σ[w(F o 2 ) 2 ] 1 / 2 ; R1 is the residual factor, F o is the observed structure factor, F c is the impact factor of the calculation, and wR2 is the weighted residual factor.

[0078] M-Et (M=Fe,Co,Ni,Cu) belongs to The same space group has similar structures, so we take Cu-Et as an example to illustrate its structural characteristics. Figure 1 As shown in a, the basic structural unit of Cu-Et is an Anderson cluster, with six O atoms around it symmetrically replaced by two triol ligands with ethyl groups at the ends. Each triol ligand-modified Anderson cluster is connected to four Na atoms by two terminal O atoms arranged at right angles. + connection. Figure 1 As shown in b, each Na + The three adjacent Anderson-type clusters interact almost perpendicularly, facing each other, effectively minimizing the steric hindrance between clusters and promoting maximum aggregation around the cation. + The specific arrangement of the clusters promotes the formation of secondary assembly structures with hollow cubic geometry, in which the cluster bodies serve as bridging units (see Figure 1 c). This cube can be simplified as follows Figure 1 The schematic diagram shown in (d) is further connected to each other through Na-O bonds to form a 3D skeleton with regular pores running through it (see Figure 1 e). For the samples M-OH (M=Fe, Co, Ni, Cu), except for Cu-OH, they are similar to M-Et in basic structure, secondary assembly structure and final arrangement, except that the terminal group of the triol ligand is changed from ethyl to hydroxyl. However, the case of Cu-OH is different: although a Na + It is still surrounded by three Anderson-type clusters similar to the other samples, but each cluster is only connected to two Na + connected, leaving the opposite side empty (see Figure 1 f). This structure still forms a hollow cubic structure, but due to the absence of some Na + , these cubes cannot form additional connections via Na-O bonds and can therefore be considered as independent cages (see Figure 1These cages have a similar three-dimensional hollow skeleton stacking model as Cu-Et ( Figure 1 h). The difference between them is that each cubic unit in Cu-Et is identical and closely packed by sharing all faces, while in Cu-OH, each cubic unit does not share any faces. Because the distance between adjacent cubes in Cu-OH is the same as the side length of the cube, they form a packing model similar to the close packing of cubes. It is worth noting that the Na in Cu-OH + The asymmetric connection type also leads to a change in the space group from one with higher symmetry to to a less symmetric In addition to single crystal X-ray diffraction analysis, FT-IR spectroscopy was used to confirm the structure of these frameworks. Figure 2 As shown, at 3500~1000cm -1 The identified signals between 950 cm -1 The nearby signals evidence the formation of polyoxometalates, indicating the presence of inorganic clusters along with organic components.

[0079] These eight ionic frameworks were synthesized in aqueous solution and their thermal stabilities were evaluated by thermogravimetric analysis. Figure 3 As shown, the weight of all compounds gradually decreases with increasing temperature, indicating that the organic components gradually decompose. Given that these ionic frameworks are prepared for gas separation, they need to be pretreated by heating at around 105°C. Therefore, the focus is on evaluating the stability performance of these ionic frameworks below this temperature. The thermal gravimetric curves show that the weight loss of the eight ionic frameworks does not exceed 1% before reaching 105°C, which is attributed to the evaporation of free water, thus confirming the integrity of the structure at low temperatures. In order to further study the effect of heating on structural integrity, each ionic framework was heated at 105°C for 8h and then analyzed by PXRD. As shown Figure 4 As shown in Figure 2, each ionic framework exhibited similar diffraction patterns before and after heating, which illustrates the high thermal stability of the ionic framework structure. In addition to the thermal stability evaluation, the effect of humidity on the ionic framework was also evaluated using PXRD analysis. Figure 5 As shown, no significant changes were observed in the PXRD pattern as the humidity increased from 60% to 90%, indicating that the ionic framework structure has good stability under high humidity conditions. This property makes the ionic framework useful for the adsorption or separation of humid gases.

[0080] Since the ionic skeleton is based on Na + and clusters, so upon exposure to water, due to the Na +The strong hydration process cannot maintain its packing arrangement, which leads to the separation of anions and cations. This raises questions about their stability in organic solvents. The ionic frameworks were immersed in methanol (CH3OH), hexane (C6H 14 ), acetonitrile (CH3CN), dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) for 2 days, and its structure was examined by PXRD. Figure 6 As shown, the XRD patterns of the eight ionic skeletons show that in CH3OH, C6H 14 After immersion in DMSO, CH3CN and DMF, the positions of the diffraction peaks remained almost unchanged, indicating its high solvent stability. Compared with the other tested organic solvents, immersion in DMSO resulted in a weaker PXRD pattern, indicating a decrease in crystallinity.

[0081] Example 2, single gas adsorption;

[0082] The gas adsorption temperatures were 273 K and 298 K, respectively, and the pressure range was 0 to 1 bar. Before the gas adsorption test, 100 mg of the sample was degassed and activated at 105 °C and immediately transferred to a BSD-PM (3H-2000PM) gas adsorption analyzer for single-component gas adsorption testing.

[0083] N2 adsorption-desorption isotherms were measured at -196 °C on a Micromeritics TriStar II 3020 analyzer, and the samples were degassed under vacuum at 150 °C for 6 h before measurement. The surface area was calculated using the adsorption data in the relative pressure range (P / P0) of 0.05 to 0.30 according to the following Brunauer-Emmet-Teller (BET) equation:

[0084]

[0085] Where P0 is the saturation pressure; P / P0 is the relative pressure; C and N m are constants related to the energy of adsorption and monolayer loading, respectively; N is the adsorption loading. The pore size distribution was calculated using the density functional theory (DFT) method, and the micropore volume and total pore volume were also calculated using the same method.

[0086] result:

[0087] 1) BET specific surface area and pore size of ionic skeleton: For porous structures, BET specific surface area and pore size are important physical parameters. Except for Cu-OH, the other seven ionic skeletons have the same stacking model, so Cu-Et and Cu-OH are selected as examples. N2 adsorption isotherm test was performed at 77K to calculate the specific surface area, and CO2 isotherm adsorption test was performed to obtain pore size distribution data. Figure 7As shown in a and c, the N2 adsorption isotherms of Cu-Et and Cu-OH at 77K are both type I curves, indicating that there are permanent pores of micropore size in the ionic skeleton. The BET specific surface areas of Cu-Et and Cu-OH are calculated to be 110.70 m 2 / g and 125.60m 2 / g. Figure 7 As shown in b and d, pore size analysis shows that the actual pore size of Cu-Et is The actual pore size of Cu-OH is Compared with the value in single crystal structure ( and The presence of permanent pores in the ionic framework ensures its ability to adsorb gases.

[0088] 2) Gas adsorption performance of ionic skeleton: Figure 8 Middle a and Fig. 9 As shown in the figure, all eight framework materials show significant SO2 adsorption capacity at 273K. These framework materials have similar adsorption behaviors: the amount of SO2 adsorbed gradually increases with the increase of pressure from 0 to 1 bar, and reaches a relatively stable state at high pressure, which indicates a type I isothermal adsorption characteristic. This isothermal adsorption curve is generally consistent with the adsorption behavior of microporous materials, which have high specific surface area and small pore size and show obvious saturation adsorption characteristics. All observed adsorption behaviors are highly correlated with the microstructure derived from single crystal X-ray diffraction analysis.

[0089] Despite similar adsorption behaviors, there are significant differences in the adsorption amounts between these compounds. Take the adsorption amount of SO2 at 1 bar as an example (see Figure 8In b), it can be seen that Cu-OH achieves the highest adsorption amount of 7.00mmol / g, while Ni-Et only reaches 2.55mmol / g, indicating that there are significant differences in the performance of the eight ionic framework structures. The overall trend shows that the adsorption capacity of M-OH is superior to that of the corresponding M-Et compound, indicating that the terminal group has a significant effect on the adsorption amount. In addition, the heteroatom in the center of the Anderson-type cluster plays a key role in the SO2 adsorption process, among which the Cu-centered polymetallic oxygen cluster performs better than other polymetallic oxygen clusters, while the Ni-centered polymetallic oxygen cluster shows a poor performance level. It is worth noting that the terminal group can enhance or reduce the effect of the central heteroatom on SO2 adsorption. For the framework structure with Et as the terminal, there is an improvement ratio of 108.2% from the lowest adsorption performance of Ni-Et (2.55mmol / g) to the highest adsorption performance of Cu-Et (5.31mmol / g). In contrast, for the OH-terminated framework structure, the improvement ratio from the lowest adsorption performance of Ni-OH (5.02mmol / g) to the highest adsorption performance of Cu-OH (7.00mmol / g) is only 39.4%. In order to further explore the adsorption capacity of polar bond gases in these frameworks, we selected NH3 as another representative molecule for evaluation. Figure 8 Medium c and Fig.10 As shown in the figure, at 273K and in the pressure range of 0 to 1 bar, the isothermal adsorption curve of NH3 is similar to that of SO2, and also shows type I isothermal adsorption, which further proves that the prepared ionic skeleton has a microporous structure. Figure 8 As shown in (d), the NH3 adsorption capacity of the eight ionic skeletons is significantly higher than that of SO2. Among them, Cu-OH shows the best NH3 adsorption performance at 13.60mmol / g, which is almost twice its corresponding SO2 adsorption capacity. In addition to the Cu-central skeleton, other ionic skeletons Fe-OH, Co-OH and Ni-OH also show similar ammonia adsorption capacity as SO2, with adsorption capacities ranging from 8.41 to 9.70mmol / g. For NH3 adsorption, although the OH-terminal skeleton is still better than the Et-terminal skeleton, the difference between the two becomes very small, and the NH3 adsorption capacity of Ni-OH is only 0.22mmol / g greater than that of Ni-Et. From the perspective of central heteroatoms, the adsorption capacity of the Cu-central skeleton is significantly better than that of other central skeletons, and this phenomenon also occurs in SO2 adsorption.

[0090] The adsorption capacities of SO2 and NH3 show that the M-OH framework is consistently superior to its M-Et counterpart, thus making M-OH a suitable candidate for capturing other gases. In addition, the Cu-centered framework exhibits superior adsorption performance, and the adsorption capacity of Cu-Et was also further evaluated. Taking Cu-OH as a representative example (see Fig.11In a), the isothermal adsorption curves of O2 and CH4 almost overlap, showing a very limited adsorption capacity. Although Cu-OH has a relatively strong adsorption capacity for CO compared to O2 and CH4, its adsorption capacity at 1 bar is still low, only 0.70 mmol / g, which is only about 10.0% of the adsorption capacity of SO2 under the same conditions. Similar trends were also observed in the gas adsorption results of Cu-OH for N2 and H2 (see Fig.11 b). Fig.11 As shown in Figure b, from 0 to 1 bar, the isothermal adsorption curves of Cu-OH for N2 and H2 are almost linear, and the adsorption amounts are very small. At 1 bar, the N2 adsorption and H2 adsorption amounts of Cu-OH are 0.48 mmol / g and 0.06 mmol / g, respectively, which are only 3.5% and 0.4% of the NH3 adsorption amounts, indicating that it may have a high separation ratio in NH3 / N2 and NH3 / H2 mixed gases. In addition to Cu-OH, other ionic skeletons such as Fe-OH, Co-OH, Ni-OH and Cu-Et have also been evaluated for their ability to capture CO, O2, CH4, N2 and H2 gases. Fig.12 As shown in Figure 2, these ionic frameworks exhibit similar trends, where the isothermal adsorption curves of O2 and CH4 are closely aligned at low levels. In addition, the adsorption value of CO is relatively high, with Ni-OH achieving the best performance at an adsorption amount of 1.13 mmol / g. Regarding N2 and H2, as Fig.13 As shown, these ionic frameworks show negligible capacity with almost no distinguishable isotherms, reflecting very low adsorption amounts. The isotherm adsorption curves of the above gases show that these ionic frameworks exhibit strong adsorption capacity for highly polar bonded gases such as SO2 and NH3, while adsorption of non-polar or low polar bonded gases such as O2, CH4, CO, N2 and H2 is very small. This characteristic gives these ionic frameworks significant potential in the separation of binary gas mixtures such as SO2 / CO, SO2 / O2, SO2 / CH4, NH3 / N2 and NH3 / H2.

[0091] Example 3, penetration test;

[0092] The penetration test was carried out on the mixed gases SO2 / CO, SO2 / O2, SO2 / CH4, NH3 / N2, NH3 / H2 with volume ratios of 50:50 and 3:97, and the temperature and pressure were 298K and 1bar, respectively. Active Cu-OH (100mg) was added to the column and activated by helium blowing at 378K for 2h. After the column was cooled to the predetermined temperature, the mixed gas was passed at a flow rate ratio of 20mL / min. The separated gas was recorded by a mass spectrometer.

[0093] Results: The penetration test was carried out using a mixture of SO2 / CO, SO2 / O2, and SO2 / CH4 with a volume ratio of 3:97. The results are as follows Fig.14 As shown in Figures ac, when these mixed gases pass through the Cu-OH powder, CO, O2, or CH4 are detected almost immediately in the outflow due to the weak adsorption affinity of Cu-OH for these gases. In contrast, SO2 is not detected initially but is effectively adsorbed by Cu-OH from the beginning. As the amount of adsorbed SO2 increases with time until the interior of the framework is saturated, its concentration in the outflow gas subsequently rises. When dynamic adsorption equilibrium is reached, the composition of the outflow gas is consistent with the original mixed gas. For NH3 / N2 and NH3 / H2 mixed gases (also in a volume ratio of 3:97, see Fig.14 In Figures d and e), N2 and H2 are detected quickly in the outflow, while NH3 is first adsorbed by the ion framework and then released after the saturation stage. Although all five gas mixtures can be effectively separated by Cu-OH, significant differences emerge when considering the presence of SO2 or NH3, such as Fig.14 As shown in Fig. 5, the breakthrough point of SO2 is significantly higher than that of NH3. Considering the lower absorption rate and longer residence time of SO2 in Cu-OH, it can be inferred that NH3 has a stronger affinity for Cu-OH than SO2 and shows a faster adsorption process. It is worth noting that at a volume ratio of 1:1, the mixed gases SO2 / CO, SO2 / O2, SO2 / CH4, NH3 / N2 and NH3 / H2 can also be separated efficiently by Cu-OH ( Fig.15 ).

[0094] The eight ionic frameworks all showed high adsorption capacity for SO2 and NH3, and their stability before and after gas adsorption was evaluated by PXRD patterns. Fig.16 As shown in Figure 2, the PXRD peak positions of these skeletons hardly changed before and after SO2 adsorption, indicating that their structures remained stable. Similar situations can also be found during NH3 adsorption ( Fig.17 ), which further proves the high stability of the ionic framework. In order to further evaluate the availability of the ionic framework in SO2 and NH3 adsorption, five cyclic adsorption experiments were carried out on Cu-OH for single component SO2 and NH3, and PXRD tests were performed after the cyclic experiments to evaluate the structural changes. Fig.18 As shown, the SO2 capture capacity of Cu-OH remained almost unchanged during the five adsorption / desorption cycles, indicating that Cu-OH has high adsorption stability and can be reused at least five times. The PXRD patterns of Cu-OH before and after five cycles of SO2 adsorption are roughly the same, showing high structural integrity during the adsorption process ( Fig.18a and b). For NH3, Cu-OH can also undergo at least 5 cycles of adsorption and desorption, and the curve hardly changes. The corresponding PXRD results further prove its high stability ( Fig.18 c and d). All these advantages ensure that the ionic framework can be used as an efficient SO2 and NH3 adsorbent.

[0095] Example 4, gas adsorption mechanism of ionic framework;

[0096] All eight frameworks have strong adsorption capacity for SO2 and NH3, which can be adjusted by the central heteroatom and the terminal groups of the Anderson-type polyoxometalates. On the other hand, these frameworks hardly adsorb CO, O2, CH4, N2 and H2, so it is crucial to understand the factors affecting adsorption and the adsorption mechanism.

[0097] 1) Factors affecting gas adsorption;

[0098] a. Influence of pore size and chemical environment of ionic skeleton: It is well known that pore size has a significant effect on gas adsorption performance in skeleton materials and plays a vital role in the adsorption amount. + Anderson-type clusters decorated with triol ligands form three-dimensional permeation channels. Since the structural units and stacking models are almost the same, the main factor affecting the pore size is the end group. However, the end groups used here are ethyl and hydroxyl, which have similar sizes but different chemical environments, and are therefore not suitable for studying the effect of pore size. In order to accurately evaluate the effect of pore size, four Fe 2+ 、Co 2+ 、Ni 2+ and Cu 2+ The skeleton has a methyl group as the terminal group as a heteroatom and is named M-Me (M = Fe, Co, Ni, Cu). The SO2 and NH3 adsorption properties of M-Me are shown in Fig.19 , the adsorption-desorption curve of M-Me is similar to that of M-Et, belonging to type I adsorption. Fig. 20The SO2 and NH3 adsorption amounts of M-Me and M-Et are shown, and it can be seen that the adsorption amount of M-Me at 1 bar is slightly greater than that of M-Et. Because the methyl and ethyl groups provide the same chemical environment, and the only difference between the Me- and Et-terminated frameworks is the size of the pores, which plays a decisive role in the amount of gas adsorption. This means that under similar chemical environment conditions, a larger pore size can actually improve the gas adsorption performance. In addition to the pore size, the chemical environment also plays an important role in the gas adsorption process. As shown above, the Et- and OH-terminated frameworks have similar pore sizes, but their ends have a great influence on the chemical environment of the pores in the framework, resulting in differences in the adsorption amount. Compared with the ethyl group, the hydroxyl group has a higher polarity and stronger activity, and can more easily produce relatively strong interactions with SO2 and NH3, which is conducive to improving the gas adsorption performance. Therefore, optimizing the microenvironment of the pores and adjusting the properties of the polarity are crucial to improving the gas adsorption performance of the ionic framework.

[0099] b. Effect of temperature on gas adsorption performance: Temperature is a key parameter in the gas adsorption process and has a significant impact on the adsorption amount. In most cases, gas adsorption is an exothermic process because the gas molecules move toward the solid surface and their molecular motion speed is significantly reduced, thereby releasing heat. Therefore, with the increase of temperature, the adsorption equilibrium tends to move in the opposite direction, resulting in a decrease in the adsorption amount. However, high temperature is also conducive to the increase in the motion speed of the adsorbed molecules, which can accelerate the adsorption rate before reaching saturation. Although adsorption may be more sufficient at low temperatures, it takes a longer time to reach adsorption equilibrium. In some specific adsorption processes, especially when it is difficult to reach adsorption equilibrium at low temperatures, appropriately increasing the temperature may promote the adsorption process in a short period of time, especially for those adsorption processes that are diffusion-controlled. Therefore, it is of great significance to study the role of temperature in the gas adsorption process through the ion skeleton. In order to illustrate the effect of temperature on gas adsorption, the isothermal adsorption curves of SO2 and NH3 at 273K and 298K were compared, and the adsorbent used was Cu-OH. As Fig.21 As shown in Figure a, the isothermal adsorption curve of SO2 at 298K shows a faster saturation trend than that at 273K, which indicates the acceleration of molecular motion. However, it should be noted that high temperature often weakens the attraction of the adsorbent to gas molecules, causing the adsorption equilibrium to move toward the desorption direction, so the adsorption amount at high temperature is lower than that at low temperature. The isothermal adsorption curves of NH3 at different temperatures also show a similar situation ( Fig.21 (b) In the low-pressure region (below 0.1 bar), the amount of NH3 adsorbed at 298 K is greater than that at 273 K, which indicates that the diffusion process in the initial stage is accelerated with increasing temperature.

[0100] 2) Theoretical calculation of adsorption process;

[0101] As mentioned above, the pore size and temperature of the framework significantly affect the gas adsorption performance. In the series of frameworks reported, the central heteroatoms of the cluster also play a key role in gas capture. It is worth noting that these central heteroatoms are in a fully coordinated state, and their coordination sites are occupied by two triol ligands. Therefore, they have no chance to interact with the adsorbed gas through coordination bonds. To verify the role of the central heteroatoms in gas adsorption, density functional theory (DFT) simulations were performed using the freely available CP2K / Quickstep software package to calculate the adsorption energies of NH3 and SO2. The Perdew-Burke-Ernzerhof density functional with Grimme D3 dispersion correction was used. The 2s, 2p electrons of O, N and C and the 4s electrons of Zn were regarded as valence, and the remaining core electrons were represented by Goedecker-Teter-Hutter (GTH) pseudopotentials. The Gaussian basis set was double ζ with a set of polarization functions (DZVP-MOLOPT-SR-GTH), and the plane wave cutoff was set to 400Ry. The Broyden-Fletcher Goldfarb-Shanno (BFGS) minimizer optimizes the geometry.

[0102] a SO2 and NH3 adsorption energy of M-OH: Considering that M-OH exhibits stronger adsorption capacity than M-Et, the DFT method is used to study their adsorption energies. Adsorption energy is a key parameter for evaluating adsorption stability, and lower adsorption energy indicates higher adsorption tendency. Fig. 22 As shown in a and b, the SO2 absorption energies of Fe-OH, Co-OH, Ni-OH, and Cu-OH are -65.23, -38.88, -31.04, and -93.87 KJ / mol, respectively, indicating that Cu-OH shows the highest gas affinity consistent with the experimental results. A similar trend was observed for the adsorption energy of NH3, where the NH3 adsorption energy of Cu-OH is -114.85 KJ / mol, while the adsorption energy of Ni-OH is -95.00 KJ / mol. These results indicate that although the central heteroatoms do not directly capture the gas, they significantly affect the adsorption of the gas by providing different levels of adsorption energy.

[0103] In addition to adsorption energies, DFT can also simulate the approximate adsorption locations of NH3 and SO2 gases in the ionic framework. Fig. 22As shown in a, the positive and negative ions in M-OH generate a local electric field in the pore, thus forming a potential difference. NH3, as a molecule with polar bonds, has a lone pair of electrons on its nitrogen atom, which tends to bind to the positively charged or electron-deficient regions of the adsorbent material. Similarly, SO2 is also a gas with polar bonds. The sulfur atom exhibits a slightly positive charge characteristic, which promotes electron acceptance, while the oxygen atom has a slight negative charge and interacts with the positively charged or electron-deficient regions on the adsorbent material. Therefore, the best adsorption sites for the two gases are located in areas with a larger charge distribution inside the framework. These areas provide stronger electrostatic interactions, thereby enhancing the adsorption of the gas. This clarifies how gas molecules interact with the ionic framework and ligands, and is crucial to understanding the mechanism of selective adsorption.

[0104] b. Adsorption energy of Cu-OH for other gases: DFT calculations show that Cu-OH has a strong affinity for SO2 and NH3, which is reflected in their adsorption energy, resulting in high adsorption of these two gases. On the other hand, Cu-OH has a low adsorption capacity for CO, O2, CH4, N2 and H2, so these gases can be effectively separated from SO2 and NH3, achieving efficient separation results, as shown in the breakthrough experiments. DFT calculations are also applied to these gases to illustrate their absorption energy on Cu-OH. Fig.23 As shown, the adsorption energies of CO, O2, CH4, N2 and H2 on Cu-OH are -34.06, -23.28, -20.57, -25.30 and -13.68 KJ / mol, respectively, which are obviously weaker than the adsorption energies of SO2 (-93.87 KJ / mol) and NH3 (-114.85 KJ / mol). These findings indicate that Cu-OH has better adsorption of SO2 and NH3 than CO, O2, CH4, N2 and H2, thus effectively achieving the separation of mixed gas pairs such as SO2 / CO, SO2 / O2, SO2 / CH4, NH3 / N2 and NH3 / H2.

[0105] 3) Gas adsorption mechanism of the framework;

[0106] From both experimental and theoretical perspectives, the framework showed better adsorption performance for SO2 and NH3 than for CO, O2, CH4, N2, and H2. To understand this phenomenon and clarify the adsorption mechanism, the structural features of the framework and the properties of the gases were carefully examined. The building blocks of the prepared framework are Na + and Anderson-type polyanions, which assemble to form an ordered porous structure through ionic interactions. The separation of positive and negative centers within the framework generates a potential difference within the pores, which promotes the adsorption of gases with suitable bond sizes and polarity by the ionic framework. Table 3 shows the physical properties of these gases, including bond polarity and kinetic diameter, as well as the adsorption amount when using Cu-OH as the adsorbent.

[0107] Table 3. Bond polarity and kinetic radius of gas molecules and their adsorption by Cu-OH at 273 K and 1 bar

[0108]

[0109]

[0110] The kinetic radii of these gases are all smaller than the pore size of the ion skeleton, indicating that they may be adsorbed. In addition, there is no obvious positive or inverse relationship between the kinetic radius and the adsorption value, proving that the kinetic radius is not the decisive factor affecting the adsorption amount. On the other hand, when gases with high bond polarity are used, they can be more effectively adsorbed by the skeleton. For those gases with no or low polarity bonds, such as CO, O2, CH4, N2 and H2, their interactions with the skeleton are weak and they cannot be captured. In order to verify this concept, two gases with different polarity bonds were further analyzed. Fig.24 As shown in Figure 2, the adsorption of Cu-OH for H2S with high bond polarity is relatively high, while the adsorption for C2H2 with low polarity is relatively low. These results together indicate that the gas adsorption of ionic frameworks is mainly based on polar bond selectivity.

[0111] in conclusion:

[0112] The present invention adopts simple alkali metal ion Na + and Anderson-type polyoxometalates, and constructed a series of ionic frameworks based on ionic interactions. The prepared ionic frameworks have a periodic three-dimensional arrangement and a size of approximately The regular cubic pores of Na +Due to the strong hydration of Cu-OH, the anions and cations in the framework dissociate in the aqueous solution, causing the structure to dissolve in water, which in turn affects its stability. However, in organic solvents, these ionic frameworks can exist in the form of insoluble precipitation, thereby maintaining the stability of their structure. In addition, these ionic frameworks also show significant thermal stability and moisture resistance, and can maintain structural integrity at temperatures not exceeding 105°C and humidity of 90%. It is worth noting that these ionic frameworks show good gas adsorption capacity for acidic gas SO2 and alkaline gas NH3. Specifically, under the conditions of 1 bar and 273K, the SO2 adsorption capacity of Cu-OH reaches 7.00mmol / g, and the NH3 adsorption capacity reaches 13.60mmol / g. In addition, the framework has excellent recycling performance, and its gas adsorption capacity remains basically unchanged after 5 adsorption-desorption cycles. In contrast, the adsorption capacity of the ionic framework for gases such as CO, O2, CH4, N2 and H2 is relatively low. This characteristic makes the ionic skeleton highly selective in separating mixed gases SO2 / CO, SO2 / O2, SO2 / CH4, NH3 / N2 and NH3 / H2. Further DFT calculation results show that when the adsorbed gases are SO2 and NH3, the skeleton containing the central heteroatom Cu shows the strongest affinity, which is consistent with the highest adsorption amount shown in the experimental results. By comparing the adsorption capacity of different gases, it can be clearly seen that the interaction between the ionic skeleton and SO2 and NH3 is stronger than its interaction with CO, O2, CH4, N2 and H2, thereby enhancing the adsorption effect of the ionic skeleton on SO2 and NH3. After analyzing the physical properties of the adsorbed gas, it was found that when the gas size is appropriate, the ionic skeleton has a strong adsorption capacity for gases with high polar bonds, while showing very little affinity for gas molecules with no or low polar bonds. This difference in gas adsorption based on polarity may originate from the electric field gradient generated by the separation of positive and negative charges within the ionic skeleton. In summary, the present invention not only provides an experimental and theoretical basis for polarity-based gas adsorption and separation, but also provides valuable insights and inspiration for gas separation targeting different polar bonds.

[0113] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing an ionic framework with selective adsorption, characterized in that: The ionic framework is composed of Na + and Anderson type polymetallic oxygen clusters, the ionic framework comprising: Fe-Et, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [FeMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O; Co-Et, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [CoMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O; Ni-Et, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [NiMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O; Cu-Et, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [CuMo6O 18 [CH3CH2C(CH2O)3]2]·1.3H2O; Fe-OH, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [FeMo6O 18 [HOCH2C(CH2O)3]2]; Co-OH, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [CoMo6O 18 [HOCH2C(CH2O)3]2]; Ni-OH, whose molecular formula is Na 4 / 3 (NH4) 8 / 3 [NiMo6O 18 [HOCH2C(CH2O)3]2]; Cu-OH, whose molecular formula is Na 2 / 3 (NH4) 10 / 3 [CuMo6O 18 [HOCH2C(CH2O)3]2]; The preparation steps of Fe-Et are as follows: 2mmol FeSO4·7H2O, 2mmol (NH4)6Mo7O 24 4H2O and 4mmol 1,1,1-trimethylolpropane were dissolved in 23mL buffer solution of CH3COONa / CH3COOH, and the mixture was heated to 80°C for 2h under continuous stirring; then, the mixture was filtered in a hot state to obtain a filtrate; the filtrate was evaporated by leaving it open at room temperature for 2 days to obtain crystals; The preparation step of Co-Et is as follows: replacing FeSO4·7H2O in the preparation step of Fe-Et with CoSO4·7H2O; The preparation steps of Ni-Et are as follows: replacing FeSO4·7H2O in the preparation step of Fe-Et with NiSO4·6H2O; The preparation step of Cu-Et is as follows: replacing FeSO4·7H2O in the preparation step of Fe-Et with CuSO4·5H2O; The preparation step of the Fe-OH is as follows: replacing 1,1,1-trimethylolpropane in the preparation step of Fe-Et with pentaerythritol; The preparation step of Co-OH is as follows: replacing 1,1,1-trimethylolpropane in the preparation step of Co-Et with pentaerythritol; The preparation step of Ni-OH is as follows: replacing 1,1,1-trimethylolpropane in the preparation step of Ni-Et with pentaerythritol; The preparation step of Cu-OH is as follows: 1,1,1-trimethylolpropane in the preparation step of Cu-Et is replaced by pentaerythritol.

2. A method for using the ionic framework with selective adsorption prepared by the preparation method according to claim 1 as a gas adsorbent in adsorbing gases with polar bonds, characterized in that: The gas having a polar bond includes SO2 and NH3.